JEJAK AUSTRONESIA DI MAMASA, SULAWESI BARAT: KAJIAN TRADISI TUTUR, ETNOGRAFI, DAN ARKEOLOGIS - Budianto Hakim (WalennaE, 2009)
Austronesian speakers do not just settle along Das Karama, Mamuju, but also spread to other mas in South and West Sulawesi. Austronesian settlers spread into a number of places due to several factors, including factors of land, security and others. Landscape of a residence be the deciding factor, because the community is Austronesian farming communities that require land suitable for agricultural development, especially domestication tubers, grains and livestock. From the safety factor, the possibility of migration of one group to another, for trying to protect the group from other groups attack.Penutur Austronesia tidak hanya berdiam di sepanjang Das Karama, Kabupaten Mamuju, tetapi juga menyebar ke daerah lainnya di Sulawesi Selatan dan Barat. Pemukim Austronesia menyebar ke sejumlah tempat karena beberapa faktor, termasuk faktor alam, keamanan dan lainnya. Lansekap tempat tinggal menjadi faktor penentu, karena masyarakat Austronesia adalah masyarakat petani yang membutuhkan tanah yang cocok untuk pengembangan pertanian, terutama domestikasi umbi-umbian, padi-padian dan ternak. Dari faktor keamanan, kemungkinan migrasi dari satu kelompok ke kelompok lain, untuk mencoba melindungi kelompok dari kelompok lain.